The Role of Authentic Texts in Vocabulary Development - Nigora, Rakhmatova (Journal of Research in Innovative Teaching and Inclusive Learning, 2024)
This research work is an attempt of a beginning EFL teacher to prove the effectiveness of using authentic materials in the development of vocabulary proficiency in English. To reach the central goal of the investigation, the researcher experiments authentic materials in a practical language-teaching context (Vocabulary in Context). The subjects of the research are two groups of first-year UWL students. During two months of actual teaching, which was a significant step of the research for it provided the researcher with reliable data, the groups were exposed to two different types of course materials-authentic (materials form mainly certain types as newspapers and magazines) and course book texts. Specially designed Pre- and Post-Tests were used as tools of comparing the effect of both types of materials on the subjects’ vocabulary ability. In addition, the subjects’ attitude toward the authentic materials used during the course was thoroughly studied by the means of Questionnaire. The research found authentic texts to be more effective in the development of subjects’ vocabulary proficiency in comparison with their traditional course book materials.